IMPLEMENTASI PROGRAM MODEL DISIPLIN (MODIS) SEBAGAI UPAYA PEMBENTUKAN KARAKTER DISIPLIN, TANGGUNG JAWAB, DAN PEDULI PADA PESERTA DIDIK DI SMP NEGERI 20 JAKARTA - Rastri; Budiaman; Dian Alfia Purwandari (STKIP Subang, 2026)
Character building among students remains a significant challenge in education; a 2024 KPK survey revealed that 62.29% of students submitted assignments late and 46.16% arrived late to school, reflecting a lack of internalized values ​​regarding discipline, responsibility, and care. This situation prompted SMP Negeri 20 Jakarta to develop the Discipline Model Program (MODIS) re-launched in August 2025 within the framework of the KPK’s PERISAI Program. This study analyzes the implementation of the MODIS Program in fostering discipline, responsibility, and care among students, as well as the factors influencing the internalization of these values. A qualitative method was employed, with data collected through semi-structured interviews, observation, documentation review, and literature studies. Informants comprising key and core participants were selected using purposive sampling. Data validity was verified through source and technique triangulation. The results indicate that the MODIS Program successfully shapes student character through three stages of social construction, although the level of value internalization varies among individuals. Internal factors include motivation, willingness, and habits, while external factors encompass the family, school, and community environments. These findings contribute to the development of habituation-based character education programs.